Hubungan Kecerdasan Emosional dan Kemampuan Menghafal Juz’amma terhadap Prestasi Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadist Kelas IV di MIN 1 Pati - Hasanah, Rohmatul; Auliya, Nanang Nabhar Fakhri (Lembaga Yasin AlSys, 2022)
This study aims to: (1) determine the level of emotional intelligence of students at MIN 1 Pati (2) To determine the level of ability to memorize juz'amma students at MIN 1 Pati (3) To determine the level of learning achievement of students at MIN 1 Pati (4) Knowing the relationship between emotional intelligence and the ability to memorize juz'amma on student achievement in the fourth grade Al-Qur'an Hadith subject at MIN 1 Pati.This type of research is quantitative with a correlational approach. Sources of data obtained through questionnaires and report cards of the respondents. The author conducted a field study at MIN 1 Pati, namely in the class IV scope. Collecting questionnaire data, report cards and documentation. The population in this study were 84 students. The sample used a cluster random sampling technique, consisting of 40 students in grade IV A. After the data collection process, data analysis was carried out starting with validity tests, reliability tests, descriptive analysis, classical assumption tests including linearity tests, multiple regression significance tests, significance tests. multiple linear regression coefficient and multicollinearity test, then tested the hypothesis using the multiple correlation coefficient significance test.The results showed (1) the level of emotional intelligence in MIN 1 Pati showed a percentage of 55% in the low category. (2) the level of ability to memorize juz'amma at MIN 1 starch shows a percentage of 60% in the medium category. (3) the level of learning achievement at MIN1 Pati shows a percentage of 50% in the medium category (4) based on the results of hypothesis testing shows that the Fcount value is 15,885> from the Ftable value of 2.86 and it is known that the significance value is 0.000 <0.05, the HI hypothesis accepted Ho is rejected, it shows that the variables of emotional intelligence and the ability to memorize juz'amma have a simultaneous effect on student achievement in the fourth grade Al-Qur'an Hadith subject at MIN 1 Pati.